Kinetic Studies on Saponification of Poly(ethylene terephthalate) Waste Powder Using Conductivity Measurements. (25th August 2014) - Patil, Dilip B.; Batra, Vijendra; Kapoor, Sushil B.
Abstract : Conductometric measurement technique has been deployed to study the kinetic behavior during the reaction of poly(ethylene terepthalate) (PET) and NaOH. A laboratory made arrangement with facility of continuous stirring was used to carry out experiments at desired temperature. With conductometry, the determination of kinetic as well as thermodynamic parameters becomes more simple and faster as compared to gravimetry. Chemical kinetics of this reaction shows that it is a second order reaction with reaction rate constant 2.88 × 10 - 3  g −1  s −1 at 70°C. The specific reaction rates of the saponification reaction in the temperature range at various temperatures (50–80°C) were determined. From the data, thermodynamic parameters such as activation energy, Arrhenius constant (frequency factor), activation enthalpy, activation entropy, and free energy of activation obtained were 54.2 KJ g −1, 5.0 × 10 6  min −1, 90.8 KJ g −1, - 126.5 JK −1  g −1, and 49.9 KJ g −1, respectively.